SYSTEM ANALYSIS HYDROLITHOSPHERE PROCESSES BESHTAUGORSKY FIELD - V. V. Tsapleva; G. V. Masyutina; S. B. Sizov; T. I. Drovosekova (Современная наука и инновации, 2022)
This article describes a systematic analysis hydrolithosphere processes: a mathematical model is developed hydrolithosphere processes Beshtaugorsky field, the mathematical models describing the processes of diffusion of contaminants in ground water that involve the relevant boundary conditions from the operational layer, and also shows the stages of designing distributed control system, the analysis of the closed-loop system.